An integrated photonics engine for unsupervised correlation detection - Ghazi Sarwat, Syed; Brückerhoff-Plückelmann, Frank; Carrillo, Santiago García-Cuevas; Gemo, Emanuele; Feldmann, Johannes; Bhaskaran, Harish; Wright, C. David; Pernice, Wolfram; Sebastian, Abu (Science advances, 2022)
With more and more aspects of modern life and scientific tools becoming digitized, the amount of data being generated is growing exponentially. Fast and efficient statistical processing, such as identifying correlations in big datasets, is therefore becoming increasingly important, and this, on account of the various compute bottlenecks in modern digital machines, has necessitated new computational paradigms. Here, we demonstrate one such novel paradigm, via the development of an integrated phase-change photonics engine. The computational memory engine exploits the accumulative property of Ge2Sb2Te5 phase-change cells and wavelength division multiplexing property of optics in delivering fully parallelized and colocated temporal correlation detection computations. We investigate this property and present an experimental demonstration of identifying real-time correlations in data streams on the social media platform Twitter and high-traffic computing nodes in data centers. Our results demonstrate the use case of high-speed integrated photonics in accelerating statistical analysis methods.
Gesehen am 18.07.2022